Trends in mortality and causes of death among Chinese adolescents aged 10–19 years from 1990 to 2019 - Zhu, Jiaxin; Li, Yilu; Zhang, Chengcheng; He, Jun; Niu, Lu (Frontiers in Public Health, 2023)
Objective Promoting adolescent health is essential to achieving the goals of the Healthy China 2030 (HC 2030) initiative. As socioeconomic conditions improve and medical practices and disease patterns evolve, adolescent mortality rates and causes of death vary considerably. This study provides up-to-date data on adolescent mortality and causes of death in China, highlighting key areas of focus for investment in adolescent health. Methods Data regarding mortality and causes of death in Chinese adolescents aged 10–19 years were extracted from the Global Burden of Disease study from 1990 to 2019. The data variables were examined according to year, sex, and age. The autoregressive integrated moving average model was used to predict non-communicable disease (NCD) mortality rates and rank changes in the leading causes of death until 2030. Results The all-cause mortality rate (per 100,000 population) of Chinese adolescents aged 10–19 years steadily declined from 1990 (72.6/100,000) to 2019 (28.8). Male adolescents had a higher mortality (37.5/100,000 vs. 18.6 in 2019) and a slower decline rate (percent: −58.7 vs. −65.0) than female adolescents. Regarding age, compared with those aged 10–14 years, the mortality rate of adolescents aged 15–19 years had a higher mortality (35.9/100,000 vs. 21.2 in 2019) and a slower decrease rate (percent: −57.6 vs. −63.2). From 1990 to 2019, the rates of communicable, maternal, and nutritional diseases declined the most (percent: −80.0), while injury and NCDs mortality rates were relatively slow (percent: −50.0 and −60.0). In 2019, the five leading causes of death were road injuries (6.1/100,000), drowning (4.5), self-harm (1.9), leukemia (1.9), and congenital birth defects (1.3). Furthermore, NCDs' mortality rate decreased by −46.6% and −45.4% between 2015–2030 and 2016–2030, respectively. Conclusion A notable decline was observed in all-cause mortality rates among Chinese adolescents aged 10–19 years. In addition, the mortality rates of NCDs are projected to meet the target from the Global Strategy for Women's, Children's, and Adolescents' Health (2016–2030) and HC2030 reduction indicators by 2030. However, it should be noted that injury is the leading cause of death, with sexual and age disparities remaining consistent.